How you ask matters: evidence-based assessment connecting decentering, reappraisal, and self-reported wellbeing in a post-secondary sample - Wang, Yiyi; Chung, Joanne M.; Farb, Norman A. S. (Frontiers in Education, 2025)
Effective and efficient Wellbeing measurement is essential within the social sciences and public health. Wellbeing is described as a three-factor construct composed of Life Satisfaction, Positive Affect, and Negative Affect, yet there are few measurement models validated for the increasingly popular use of longitudinal, app-based assessment. We explored Wellbeing measurement in a postsecondary student sample, including two mechanistic indicators described in Mindfulness-to-Meaning Theory: Decentering and Positive Reappraisal. Across two studies, we compared and validated popular measurement models for each construct. The most parsimonious Wellbeing model indicated only a two-factor structure comprised of positive (e.g., happiness, life satisfaction, and flourishing) and negative dimensions (e.g., anger, sadness, and anxiety). A third study revealed that a three-factor structure for Wellbeing was only supported when sampling a greater diversity of positive emotions than the earlier studies. Furthermore, while the Mindfulness-to-Meaning pathway to Wellbeing was replicated, only some operationalizations of Decentering and Reappraisal accounted for variance in Wellbeing. Concrete recommendations for the longitudinal assessment are provided. This research contributes not only to our understanding of Wellbeing, but also informs its optimal assessment in longitudinal research such as clinical trials and experience sampling studies.